Adolescentes em conflito com a lei em Moçambique: uma análise sobre práticas e representações sociais dos diversos intervenientes do sistema de justiça juvenil - Francisco, Tomás Xavier José (2022)
The present research aims to analyze practices and social representations of the various actors of the Juvenile Justice Administration System in Mozambique, namely, judges, prosecutors, officers of the Police of the Republic of Mozambique (PRM), officers of the National Penitentiary Service (SERNAP), defenders of the Institute of Sponsorship and Legal Assistance (IPAJ), on the subject of adolescents in conflict with the law, having as spatial delimitation, the provinces of Maputo and Maputo City, Tete Province and Nampula Province. The work also includes non-state actors to better understand these practices and social representations of the actors in the juvenile justice administration system. The work carried out demonstrates that there are differences of opinion about the phenomenon of the adolescent in conflict with the law and the adolescent itself who is involved in infractions. One of the aspects that demonstrates this divergence is about the entry of adolescents into the ‟world of crime”. There is the representation that they get into crime because they are poor or vulnerable. But there is the representation of moral weakness: addiction, divorce, giving up, which boils down to the following: for some the causes are economic and for others, the cause has to do with the moral problems of the adolescents involved. There are also cases in which the causes have a mixed character, that is, the economic and moral issues of the subjects are seen as causes. Finally, the insufficiency of judicial policies for adolescent care in conflict with the law is concluded. We can see the precariousness of the conditions for serving the sentence, the absence of conditions conducive to the reintegration of young people into school and the absence of differentiated treatment of young people in prison establishments. These absences make it difficult to apply laws that provide for the less severe treatment of adolescents in conflict with the law by juvenile justice, indicating the need for significant advances in the protection of the human rights of young Mozambicans.